(untitled) (Revista de Ciências Agroveterinárias, 2007)
The aim of this work was to evaluate the efficiency of alternative products to control downy mildew in grapevine cv. Niágara Branca. The experiment was carried out at Epagri/Urussanga Experimental Station, in Santa Catarina State, Brazil, from September 2005 to February 2006. The following treatments were tested: phosphite K, phosphite PK, citric biomass, Bordeaux mixture, extract of the alga Ulva fasciata and control. The disease was evaluated by its area under disease progress curve in leafs (AUDPC), disease incidence in bunchs (ID) and productivity at harvest. The experimental design was completely randomized with four repetitions. Treatments were compared by the Duncan’s test (P5%). Bordeaux mixture reduced 59% of AUDPC in leafs and 45% of ID; phosphite K 0,2% and phosphite PK 0,2% reduced only AUDPC by 59% and 71%, compared with control, respectively. The algae U. fasciata extract 0,5% and citric biomass 0,25% didn‘t reduced disease development. Productivity was not affected by treatments.